Effect of saffron supplementation on oxidative stress parameters: A systematic review and meta‐analysis of randomized placebo‐controlled trials. Issue 10 (5th August 2021) - Morvaridzadeh, Mojgan; Agah, Shahram; Dulce Estêvão, M.; Hosseini, Ava Sadat; Heydari, Hafez; Toupchian, Omid; Abdollahi, Shima; Persad, Emma; Abu‐Zaid, Ahmed; Rezamand, Gholamreza; Heshmati, Javad
Abstract: Oxidative stress (OS), the absence of equilibrium between prooxidants and antioxidants in the body, has been shown to play a pivotal role in the initiation and progression of many diseases. Saffron has been noted for its antioxidant capacity and can be used to improve OS parameters in unhealthy patients. Our aim was to evaluate the efficacy of saffron supplementation on OS parameters in unhealthy patients in randomized controlled trials (RCTs). We searched Medline, EMBASE, Cochrane CENTRAL, Scopus, and Web of Science without language restrictions for RCTs up until April 2021. Studies were included if they compared any form of saffron supplementation to placebo or no supplementation on OS parameters in unhealthy patients. Using a random‐effects model with calculated standardized mean difference (SMD) and 95% confidence intervals (CI), we quantitatively synthesized the data. Heterogeneity was assessed using Cochrane's I 2 values. Ten randomized controlled trials were eligible for this review. Seven were included in the meta‐analysis and indicated an association between saffron intake and a statistically significant decrease in malondialdehyde (MDA) levels (SMD: −0.40; 95% CI: −0.63, −0.17; I 2  = 32.6%) and a significant increase in total antioxidant capacity (TAC, SMD: 0.24; 95% CI: 0.05, 0.42; I 2  = 00.0%). Saffron intake was shown to significantly impact MDA and TAC, indicating its beneficial properties in improving OS in unhealthy patients. However, additional RCTs are required to evaluate the effect on other OS parameters. Abstract : Saffron intake was shown to significantly impact MDA and TAC, indicating its beneficial properties in improving OS in unhealthy patients. However, additional RCTs are required to evaluate the effect on other OS parameters.